Deals and devolution: The role of local authority deals in undermining devolved decision making. (November 2022) - Morphet, Janice
The introduction of the devolved administrations (DAs) in the UK in 1999 was based on specific legal powers for this new scale of governance which included control of national and local priorities for expenditure within devolved matters. The legal powers conferred on these administrations included freedoms to determine expenditure within budgets which, in the case of DAs, included specific allocations linked to the Barnett Formula ensuring proportional allocations of UK state expenditure in a range of policy areas and later in the DAs, powers were provided to allow direct access to borrowing and raising funding through a range of means. In the period 1999–2014, DA powers were gradually increased, first in Scotland then in Wales and Northern Ireland. However, since 2014, in the DAs, UK Central Government has been using the provision of local and sub-regional 'deal' funding models, controlled by Whitehall, to gradually undermine this devolved decision making. This article discusses the role devolution and deals within the context of increasing EU principles of subsidiarity and the exercise of the UK Government's de facto and de jure powers in response. It examines the role of deals in the DAs and their lack of accountability within the UK state.